Carbon Emission Disclosure: Strategies for Addressing External Pressures in Indonesia - Wiyasto Dwi Handono; Dian Indri Purnamasari; Noto Pamungkas (Proceeding International Conference on Accounting and Finance, 2025)
Carbon emission disclosures present both opportunities and risks for companies amid the challenges posed by climate change. Efficient disclosure can be leveraged by companies as a marketing strategy to attract and maintain stakeholder trust. This study aims to analyze the influence of external pressures—namely regulatory pressure, customer and supplier pressure, and carbon performance—on corporate carbon emission disclosures. A purposive sampling method was used to identify 66 companies in Indonesia over the 2021 to 2023 period. Secondary data for this study were obtained from companies' annual and sustainability reports. Analysis was conducted using multiple linear regression. This research contributes to corporate sustainability literature by illustrating the impact of various forms of external pressure on carbon emission disclosures. The findings indicate that regulatory pressure and pressure from customers and suppliers influence carbon emission disclosures, whereas carbon performance does not show a significant impact on disclosure practices.